Redefining the Boundaries of the Sacred. Issue 1 (15th September 2020) - Reingold, Matt
Abstract : This essay considers three recent Jewish graphic novels that synthesize biblical and Rabbinic texts with exegetical illustrations. Designating these works as sacred graphic novels provides an opportunity for considering the boundaries of the genres of, and interrelationship between, sacred Jewish literature and graphic novels. The concept of sacred graphic novels is explored by analyzing J.T. Waldman's Megillat Esther, Jessica Tamar Deutsch's Pirkei Avot and Jordan Gorfinkel and Erez Zadok's The Passover Haggadah. While all three texts involve exegesis, what distinguishes these works is the integration of the actual text of the sacred writings in question. This integration changes the ways that the graphic novels are used as religious texts and religious texts as graphic novels and leads to a broader understanding of sacred Jewish literature.